Floral Induction in the Short-Day Plant Chrysanthemum Under Blue and Red Extended Long-Days - SharathKumar, Malleshaiah; Heuvelink, Ep; Marcelis, Leo F. M.; van Ieperen, Wim (Frontiers in Plant Science, 2021)
Shorter photoperiod and lower daily light integral (DLI) limit the winter greenhouse production. Extending the photoperiod by supplemental light increases biomass production but inhibits flowering in short-day plants such as Chrysanthemum morifolium. Previously, we reported that flowering in growth-chamber grown chrysanthemum with red (R) and blue (B) LED-light could also be induced in long photoperiods by applying only blue light during the last 4h of 15h long-days. This study investigates the possibility to induce flowering by extending short-days in greenhouses with 4h of blue light. Furthermore, flower induction after 4h of red light extension was tested after short-days RB-LED light in a growth-chamber and after natural solar light in a greenhouse. Plants were grown at 11h of sole source RB light (60:40) in a growth-chamber or solar light in the greenhouse (short-days). Additionally, plants were grown under long-days, which either consisted of short-days as described above extended with 4h of B or R light to long-days, or of 15h continuous RB light or natural solar light. Flower initiation and normal capitulum development occurred in the blue-extended long-days in the growth-chamber after 11h of sole source RB, similarly as in short-days. However, when the blue extension was applied after 11h of full-spectrum solar light in a greenhouse, no flower initiation occurred. With red-extended long-days after 11h RB (growth-chamber) flower initiation occurred, but capitulum development was hindered. No flower initiation occurred in red-extended long-days in the greenhouse. These results indicate that multiple components of the daylight spectrum influence different phases in photoperiodic flowering in chrysanthemum in a time-dependent manner. This research shows that smart use of LED-light can open avenues for a more efficient year-round cultivation of chrysanthemum by circumventing the short-day requirement for flowering when applied in emerging vertical farm or plant factories that operate without natural solar light. In current year-round greenhouses production, however, natural solar light during the first 11h of the photoperiod supports the short-day requirement for flowering, which so far could not be broken by photosynthetic active LED-lighting.